Effect of diet, vitamin D3 and other factors on genital prolapse recurrensce - Laktionova, Mariya; Kulzhanov, Maksut; Imasheva, Bayan; Serikkyzy, Laura; Barmanasheva, Zauresh (International Journal of Public Health Science (IJPHS), 2024)
This study addresses the pressing need for further investigation into risk factors contributing to genital prolapse recurrence, with a focus on factors like younger age and body mass index (BMI) that have been confirmed in the literature. Conducted as a cross-sectional study involving 300 post-operative cases of genital prolapse patients, the case groups comprising 210 individuals received regular gynecological check-ups every six months during the initial five years post-surgery, followed by annual visits, wherein lifestyle, diet, and laboratory values were monitored and adjusted. In contrast, the control group (90 patients) did not undergo post-operative gynecological follow-up. The results indicate that weight lifting, heavy physical work, menopause, constipation, insufficient protein intake, diseases associated with prolonged cough, and BMI are strongly associated with the likelihood of recurrent genital prolapse, while a weight reduction of 5 kg or more exhibits a protective effect (p<0.001). The established regression model proves statistically significant, explaining 84.1% of genital prolapse recurrence factors, with a sensitivity of 84.8% and specificity of 98.8%. These findings emphasize the importance of postoperative lifestyle monitoring, nutritional guidance, and immune support to reduce the risk of genital prolapse recurrence.